La stagione degli Ossi di seppia attraverso le lettere (1919-1925) - Bassi, Giulia (L’ospite ingrato, 2025)
The article investigates the different types of relationships that interact between the author’s letters and his creative work, taking the paradigmatic case of Eugenio Montale’s correspondence as an analysis. In particular, on the basis of Montale’s letters with his main correspondents in the period 1919-1925, the article traces the poetic elaboration of Ossi di seppia: the crossing of different “seasons” shows how letters were, for the author, a privileged textual space of reflection on his own poetry.